2022
DOI: 10.31083/j.jin2101026
|View full text |Cite
|
Sign up to set email alerts
|

Traditional medicine in China for ischemic stroke: bioactive components, pharmacology, and mechanisms

Abstract: Ischemic stroke is an acute cerebrovascular disease and the third most common cause of death a ter ischemic heart disease. Increasing attention is being paid to finding e fective treatments through traditional medicine. Thus, studying the traditional medicine for the treatment of ischemic stroke is of great importance. Traditional medicine in China includes traditional Chinese medicine (TCM) and other ethnic medicines, which is rich in variety and resources. This review first introduces the treatment mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 125 publications
0
7
0
Order By: Relevance
“…In case of Zhenzhu Pills, prior studies have shown that their main components are effective in treating conditions such as ischemic stroke and subacute ICH in Tibet, with minimal observable toxic side effects. [ 8 , 9 ] It has also been recorded in the Pharmacopoeia of the People’s Republic of China (2015 edition, Volume 1). [ 10 ] The mechanism has been regarded as inhibiting inflammatory response, [ 10 ] relieving lipid peroxidation, and downregulating the expression of caspase-3 in protecting the cerebral ischemia injury in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…In case of Zhenzhu Pills, prior studies have shown that their main components are effective in treating conditions such as ischemic stroke and subacute ICH in Tibet, with minimal observable toxic side effects. [ 8 , 9 ] It has also been recorded in the Pharmacopoeia of the People’s Republic of China (2015 edition, Volume 1). [ 10 ] The mechanism has been regarded as inhibiting inflammatory response, [ 10 ] relieving lipid peroxidation, and downregulating the expression of caspase-3 in protecting the cerebral ischemia injury in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…After a stroke, when oxygen or glucose is depleted in the ischemic brain tissue, high-energy phosphate compounds (e.g., adenosine triphosphate) will no longer be produced, resulting in the inability of energy-dependent processes necessary for tissue cell survival to proceed, leading to cellular damage and death [3,4]. Globally, IS is the 3rd most common cause of death after ischemic heart disease, posing a serious health risk to middle-aged and elderly people [5]. It is currently believed that the occurrence of IS has some genetic background factors, and the differential expression of multiple genes may affect the occurrence and prognosis of IS [6].…”
Section: Introductionmentioning
confidence: 99%
“…[ 20 ] Studies have shown that TCM has a good effect on IS, which can effectively prevent the occurrence of IS and delay the progress of the disease. [ 21 , 22 ] Therefore, exploring the mechanism of action of TCM in the treatment of diseases will help to make better use of TCM in the treatment of diseases. Naoshuantong capsule (NST capsule) is a classic drug for the treatment of IS, which has been widely used in clinical practice.…”
Section: Introductionmentioning
confidence: 99%